Kazakhstan CTO Club's recommended guidelines for interventional therapy for coronary chronic total occlusion - Begylan Stambol; Aleksey Kolesnikov; Marat Aripov; Bekzat Usmanov (National Scientific Medical Center, 2022)
Chronic total occlusion (CTO) disease refers to obstructive coronary artery disease, which is the degree of direct blood flow of the blood flow TIMI 0 degree of occlusion time 3 months, if there are already well-developed collaterals or bridge collaterals, the distance from the occlusion of the blood vessel TIMI blood flow > 0 degree is still considered a total occlusion disease. Previous studies have shown that 20% of patients with coronary heart disease have experienced CTO lesion from at least one vessel,  Percutaneous Coronary Intervention (PCI) surgery is called the "last fortress" in the field of coronary intervention because of the low success rate and high complications. Therefore, based on the integration of the clinical experience of our country and the analysis of relevant information and progress in research in this area, Chronic Total Occlusion Club Qazaq (Chronic Total Occlusion Club Qazaq, CTOCQ) developed a proposed method of interventional treatment of Coronary chronic total occlusion in Kazakhstan for reference to interventional doctors.